NILAI RELIGIUS DALAM NOVEL RANIA LANTUNAN CINTA DI SEPERTIGA MALAM KARYA ERIA CHUZAIMIAH DAN NASRULLAH - Sujoko Sujoko; Listiana Listiana (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to describe the religious values related to the relationship between human and God, relationship of human to humans, and the relationship between human and nature in the novel Rania Lantunan Cinta Di Sepertiga Malam by Eria Chuzaimiah and Nasrullah. This research is descriptive qualitative. The data collection technique used in this research is documentation study. In analyzing the data, content analysis technique is used. The results of this study consisted of 164 expressions. The religious value of the relationship between human and God includes the following five aspects: 1) there are 36 expressions of believing in Allah; 2) there are 44 expressions of wroshipping Allah; 3) there are 49 expressions of being grateful for His blessings; 4) there is one expression of being patient with His trials; 5) there are nine expressions of asking for forgiveness. The religious value of human to human relation includes 4 aspects, as follows: 1) there is one expression of fairness, 2) 10 expressions of helping each other, 3) eight expressions of forgiveness; and 4) five expressions of keeping promises. The religious value of the relationship between human and nature includes one aspect which only occures one time namely preserving the environment.